Legacy of fire slows carbon accumulation in Amazonian forest regrowth. Issue 7 (1st September 2005) - Zarin, Daniel J.; Davidson, Eric A.; Brondizio, Eduardo; Vieira, Ima CG; Sá, Tatiana; Feldpausch, Ted; Schuur, Edward AG; Mesquita, Rita; Moran, Emilio; Delamonica, Patricia; Ducey, Mark J.; Hurtt, George C.; et al.
Abstract : Amazonian farmers and ranchers use fire to clear land for agriculture and pasture as part of extensive land‐use strategies that have deforested 500 000 km 2 over the past 25 years. Ash from burning biomass fertilizes crops and pastures, but declining productivity often occurs after a few years, generally leading to land abandonment and further clearing. Subsequent forest regrowth partially offsets carbon emissions from deforestation, but is often repeatedly cleared and burned. In the first quantitative, basin‐wide assessment of the effect of repeated clearing and burning on forest regrowth, our analysis of data from 93 stands at nine locations across the region indicates that stands with a history of five or more fires suffer on average a greater than 50% reduction in carbon accumulation. In the absence of management interventions, Amazonian landscapes dominated by this pronounced legacy of fire are apt to accumulate very little carbon and will remain highly susceptible to recurrent burning.